2008
DOI: 10.1016/j.ydbio.2008.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Founder cells regulate fiber number but not fiber formation during adult myogenesis in Drosophila

Abstract: During insect myogenesis, myoblasts are organized into a pre-pattern by specialized organizer cells. In the Drosophila embryo, these cells have been termed founder cells and play important roles in specifying muscle identity and in serving as targets for myoblast fusion. A group of adult muscles, the dorsal longitudinal (flight) muscles, DLMs, is patterned by persistent larval scaffolds; the second set, the dorso-ventral muscles, DVMs is patterned by mono-nucleate founder cells (FCs) that are much larger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…These muscles are multinucleated and probably arise from fusing FCs and FCMs. In both cases, Duf-positive cells were observed that fused with the myoblasts that were forming aggregates around them and did not express Duf (Atreya and Fernandes, 2008;Dutta et al, 2004;Kozopas and Nusse, 2002;Soler et al, 2004). We observed that multinucleated primary myotubes arrive at the testes and express Duf and/or Sns during their further migration and differentiation between the epithelial layer and basal membrane of the testes.…”
Section: Discussionmentioning
confidence: 72%
“…These muscles are multinucleated and probably arise from fusing FCs and FCMs. In both cases, Duf-positive cells were observed that fused with the myoblasts that were forming aggregates around them and did not express Duf (Atreya and Fernandes, 2008;Dutta et al, 2004;Kozopas and Nusse, 2002;Soler et al, 2004). We observed that multinucleated primary myotubes arrive at the testes and express Duf and/or Sns during their further migration and differentiation between the epithelial layer and basal membrane of the testes.…”
Section: Discussionmentioning
confidence: 72%
“…Prominent examples include the thoracic dorsoventral muscles (DVMs), which constitute a second major set of IFMs, and the various groups of abdominal muscles, which are derived from nerve-associated myoblasts Fernandes and Keshishian, 1999;Rivlin et al, 2000;Atreya and Fernandes, 2008). We monitored the development of these different muscle types in Wsp mutant pupae and observed severe defects in the construction of all muscles examined (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…4I) when Wsp was specifically expressed in the persistent larval templates, under rp298 (duf)-GAL4 (also known as kirre -FlyBase) (Menon and Chia, 2001). Although a previous detailed study concluded that this driver is not active in myoblasts (Atreya and Fernandes, 2008), we again used the GAL80 ts /TARGET system (McGuire et al, 2004) to ensure restriction of GAL4 activity to pupal stages (see Fig. S1 in the supplementary material).…”
Section: Research Articlementioning
confidence: 99%
“…Scale bar: 400 μm for wing images; 50 μm for paraffin sections. presented by Atreya and Fernandes (Atreya and Fernandes, 2008), although their study did not focus specifically upon TDT development.…”
Section: Specification Of Tdt Muscle Fibersmentioning
confidence: 99%
“…These include the abdominal muscles, where each individual muscle is pre-figured by a cell expressing the canonical founder cell marker, dumbfounded/kirre, usually detected as an enhancer trap termed duf-lacZ, or rp298 (Ruiz-Gomez et al, 2000). Precursors of the adult indirect flight muscles also express duf-lacZ (Dutta et al, 2004), and the ablation of these founder cells significantly disturbs the formation of the DVMs (Atreya and Fernandes, 2008). Interestingly, whereas founders have been observed to prefigure adult muscle development, relatively little is known of the mechanisms responsible for their specification at this stage.…”
Section: Introductionmentioning
confidence: 99%